The Influence of Perceived Authenticity towards Purchase Intention from the Restaurant Image and Positive Emotion in Zangrandi Cafe in Surabaya - Lena Ellitan (Program MM Universitas Surabaya, 2021)
The growth of business in food & beverage makes the effort in this industry turn out to be more strictly competitive. Ice cream becomes one of the products which mayinterest new entrepreneurs in food & beverage. The newcomers put much effort tocreate the authenticity and difference from others in order to seize the attention of icecream lovers from the prior merchants. This research aims at investigating theinfluence of perceived authenticity towards people’s purchase intention from therestaurant image and positive emotion in Zangrandi Cafe on Yos Sudarso Street,Surabaya. The research took 150 customers as the samples who fulfilled therequirements such as not less than 17 years old, having tasted the ice cream inZangrandi Cafe on Yos Sudarso Street, Surabaya, having tried the ice cream inZangrandi Cafe on Yos Sudarso Street, Surabaya once in the last 3 months at least.The data gathering method used in this research is purposive sampling. Meanwhile,Structural Equation Modelling (SEM) is employed as a data analyzing technique.The results show that (1) Perceived Authenticity positively and significantly bringsinfluence towards Restaurant Image, (2) Perceived Authenticity positively andsignificantly brings influence towards Positive Emotion, (3) Restaurant Imagepositively and significantly brings influence towards Positive Emotion, (4) RestaurantImage positively and significantly brings influence towards Purchase Intention, (5)Positive Emotion positively and significantly brings influence towards PurchaseIntention, (6) also Perceived Authenticity positively and significantly brings influencetowards Purchase Intention.